2013
DOI: 10.1007/978-3-642-41335-3_6
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Study of Logic-Based Modules: Cheap Is Cheerful

Abstract: Abstract. For ontology reuse and integration, a number of approaches have been devised that aim at identifying modules, i.e., suitably small sets of "relevant" axioms from ontologies. Here we consider three logically sound notions of modules: MEX modules, only applicable to inexpressive ontologies; modules based on semantic locality, a sound approximation of the first; and modules based on syntactic locality, a sound approximation of the second (and thus the first), widely used since these modules can be extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 8 publications
(14 reference statements)
0
10
0
Order By: Relevance
“…In that sense, LKs are more closely related to semantic locality-based modules [13]. It has been observed in [15] that the difference between syntactic and semantic LBMs is not statistically significant. Our results thus suggest that the size difference between semantic LBMs and LKs is also statistically significant, although a full empirical analysis is needed to justify this conclusion.…”
Section: Discussionmentioning
confidence: 99%
“…In that sense, LKs are more closely related to semantic locality-based modules [13]. It has been observed in [15] that the difference between syntactic and semantic LBMs is not statistically significant. Our results thus suggest that the size difference between semantic LBMs and LKs is also statistically significant, although a full empirical analysis is needed to justify this conclusion.…”
Section: Discussionmentioning
confidence: 99%
“…A comprehensive study of different locality flavours [101] identified that there is no statistically significant difference in the sizes of semantic and syntactic locality modules. In contrast, [56] found that the difference in size between minimal modules (only available for acyclic EL TBoxes) and locality-based approximations can be large.…”
Section: Discussionmentioning
confidence: 99%
“…Since inseparability and CEs are very hard or even undecidable for most DLs [170,281,283], most logic-based a-posteriori module notions either apply to inexpressive DLs [168,235,241] or approximate minimal modules while guaranteeing conservativity [133,304,337]; the latter often provide further guarantees such as self-containment and depletingness [242]. Among those, locality-based modules (LBMs) [133] are particularly versatile, well-behaved [139,348], and available in the OWL API 10 ; they have recently been generalized via an approach based on Datalog reasoning [337]. 11 Other studies have investigated the size of modules depending on the chosen module notion [168,304]; further implementations exist (such as AMEX, or in the CEL reasoner; see the links in the original articles).…”
Section: Design-phase Considerationsmentioning
confidence: 99%